Abusing Supremacy in Five Poems by Czeslaw Milosz - Neneng Nurzanah; Desvalini Anwar (English Language and Literature, 2021)
This study is aimed to expose the issue about abusing supremacy which is done by the communist government toward the citizens and to know the contribution of poetic elements; irony,imagery,and symbol in revealing the issue of abusing supremacy. This analysis is related to the concept of power by Michel Foucault. The result of this analysis shows that abusing supremacy is done in two strategies; enforcing laws and using state’s apparatus